DIAGNOSTIC ASSESSMENT IN THE INDEPENDENT CURRICULUM: A LITERATURE REVIEW - Rona Rona (International Journal of Teaching and Learning, 2025)
This study is a literature review that aims to describe the concept, forms, objectives, and challenges of implementing diagnostic assessment in the Merdeka Curriculum. The method used is a literature study by collecting and analysing various sources such as journal articles, books, and educational policy documents related to diagnostic assessment. The results of the study indicate that diagnostic assessment in the Merdeka Curriculum consists of cognitive and non-cognitive assessments conducted before learning begins to identify students' strengths, weaknesses, knowledge, skills, and characteristics. The information from these assessments serves as a basis for teachers in designing adaptive and needs-based learning, thereby supporting the achievement of differentiated and personalised learning. However, the implementation of diagnostic assessment still faces a number of obstacles, such as limited teacher understanding, time, and supporting infrastructure. Therefore, continuous training and mentoring are needed so that diagnostic assessment can be optimised as the main foundation of learning in the Merdeka Curriculum.